Advanced MR Imaging after Total Hip Arthroplasty: The Clinical Impact - Khodarahmi, Iman; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2017)
Recent metal artifact reduction techniques in magnetic resonance imaging (MRI) have sparked a new aera in visualization of the peri-implant region and assessment of failing orthopaedic hardware. Modes of failure after total hip arthroplasty can be classified into four broad categories: osseous abnormalities, implant instability and dislocation, implant-associated synovitis, and soft tissue abnormalities. Although MRI is complementary to plain radiography and computed tomography to diagnose the first two categories, it is paramount to investigate the complications related to the synovium and soft tissues. We review the most common modes of failure of hip implants and the MRI characteristics of various causes of pain and dysfunction after hip arthroplasty including osseous stress reaction and fracture, implant loosening, implant instability, polyethylene wear–induced synovitis, adverse reaction to metal debris, infection, hematoma, recurrent hemarthrosis, heterotopic ossification, muscle, tendon, and nerve abnormalities, and periprosthetic neoplasms.
Keywords: hip; arthroplasty; metal artifact reduction; magnetic resonance imaging; pseudotumor